2004
DOI: 10.1002/marc.200400411
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Domain Size on Toughness of Poly(styrene‐block‐butadiene) Star Block Copolymer/Polystyrene Blends

Abstract: Summary: The toughness of poly(styrene‐block‐butadiene) star block copolymer/polystyrene (PS) blends have been investigated using the essential‐work‐of‐fracture approach. The blends show a co‐continuous or layer‐like structure of polystyrene‐rich and polybutadiene‐rich domains arising from the used extrusion process. A tough‐to‐brittle transition at a critical domain size of polystyrene‐rich domains of about 50 nm and a maximum in the non‐essential work of fracture at 20–30% PS (co‐continuous morphology) have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…The slope of the linear-fit plot of specific work of fracture against the ligament length represents bw p and has an equivalence to the J integral. [28] The equivalence between the EWF concept and R-curve concept using the J integral has been shown by Mai and Cotterell. [29] They found that EWF ¼ J Ic , the critical J value as a measure of the stable-crack initiation toughness, and bw p ¼ 1 4 (dJ/da) (for DENT specimens) where dJ/da is the slope of the J-R curve (a: actual crack length).…”
Section: Crack Toughness Behaviourmentioning
confidence: 99%
“…The slope of the linear-fit plot of specific work of fracture against the ligament length represents bw p and has an equivalence to the J integral. [28] The equivalence between the EWF concept and R-curve concept using the J integral has been shown by Mai and Cotterell. [29] They found that EWF ¼ J Ic , the critical J value as a measure of the stable-crack initiation toughness, and bw p ¼ 1 4 (dJ/da) (for DENT specimens) where dJ/da is the slope of the J-R curve (a: actual crack length).…”
Section: Crack Toughness Behaviourmentioning
confidence: 99%
“…The conceptual equivalence between bw P and dJ / da estimated from J R curves based on elastic/plastic fracture mechanics concept was shown by Mai et al [24] The energyrelated resistance against stable crack initiation (EWF or w e ) in PYFM concept has a theoretical significance for qualitative assessment. It was already reported that in case of heterogeneous polymer systems like filled polymers and nanostructured blend systems [25][26][27] the value of the resistance against stable crack initiation is strongly dominated by the matrix i.e. the major phase.…”
Section: Morphology and Phase Behaviormentioning
confidence: 99%
“…The slope of the linear-fit plot of specific work of fracture against the ligament length represents bw p and has an equivalence to the J-integral concept. [8] The equivalence between EWF concept and R-curve concept using the J integral has been shown by Mai and Cotterell. [14] They found that EWF ¼ J Ic , the critical J value as a measure of the stable-crack initiation toughness, and bw p ¼ 1/4dJ/da (for DENT specimens) where dJ/da is the slope of the J-R curve (a-actual crack length).…”
Section: Load-displacement Diagramsmentioning
confidence: 99%
“…Recently, two miscible triblock copolymers were combined to create thermoplastic elastomers (TPE) with increased tensile strength without any change in their elasticity by Lach et al [5] where novel morphologyproperty correlation could be established. The effects of the microphase morphology on the strength and stiffness of blends containing amorphous block copolymers have been reported in a few studies, [3,[6][7][8][9] but these were mainly blends with homopolymers. Recently, mechanical and fracture behaviour of partially miscible block copolymer blends of styrene-butadiene (SB) star block and styrene-b-styreneco-butadiene-b-styrene (S-SB-S) triblock copolymers have been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation